Activated protein C in epilepsy pathophysiology - Zoungrana, Linda Ines; Didik, Steven; Wang, Hao; Slotabec, Lily; Li, Ji (Frontiers in Neuroscience, 2023)
Epilepsy is one of the most common neurologic disorders that is characterized by recurrent seizures, and depending on the type of seizure, it could lead to a severe outcome. Epilepsy’s mechanism of development is not fully understood yet, but some of the common features of the disease are blood-brain barrier disruption, microglia activation, and neuroinflammation. Those are also targets of activated protein C (APC). In fact, by downregulating thrombin, known as a pro-inflammatory, APC acts as an anti-inflammatory. APC is also an anti-apoptotic protein, instance by blocking p53-mediated apoptosis. APC’s neuroprotective effect could prevent blood-brain barrier dysfunction by acting on endothelial cells. Furthermore, through the downregulation of proapoptotic, and proinflammatory genes, APC’s neuroprotection could reduce the effect or prevent epilepsy pathogenesis. APC’s activity acts on blood-brain barrier disruption, inflammation, and apoptosis and causes neurogenesis, all hallmarks that could potentially treat or prevent epilepsy. Here we review both Activated Protein C and epilepsy mechanism, function, and the possible association between them.